Urban Transformations Sustainable Urban Development Through Resource Efficiency, Quality of Life and Resilience - Kabisch, Sigrun; Koch, Florian; Gawel, Erik; Haase, Annegret; Knapp, Sonja; Krellenberg, Kerstin; Nivala, Jaime; Zehnsdorf, Andreas (Future City, 2018)
The book addresses urban transformations towards sustainability in light of challenges of global urbanization processes and the consequences of global environmental change. The aim is to show that urban transformations only succeed if both innovative scientific solutions and practice-oriented governance approaches are developed. This assumption is addressed by providing theoretical insights and empirical evidence pointing particularly at 3 concepts or qualities which are determined here as being central for achieving urban sustainability: resource efficiency, quality of life and resilience. Urban case studies from several international research projects illustrate our conceptual approach of urban transformations towards sustainable development. Thus, the book reaches far beyond a mere additive description of single case studies. It incorporates the results of condensed synthesis, resulting from comparisons and evaluations. It provides, based on cross-cutting reflection of single casesand different scales and methods of analysis, general and transferable findings. They do not only consider the scientific sphere but deliberately go beyond it discussing transferability of knowledge into practice, governance options and the feasibility of policy strategies in order to pave the way for sustainable urban transformations to happen today and in the future.